Towards understanding the role of nanomedicine in targeting TNFR2 in rheumatoid arthritis - Lambuk, Fatmawati; Nordin, Nor Asyikin; Mussa, Ali; Lambuk, Lidawani; Ahmad, Suhana; Hassan, Rosline; Kadir, Ramlah; Mohamud, Rohimah; Yahya, Nurul Khaiza (Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammation of the synovium and progressive joint destruction which significantly affects both quality of life and socioeconomic status. Admittedly, various treatments are available, but they are usually accompanied by various side effects, from mild to severe, and potentially with adverse events. Tumour necrosis factor‐alpha (TNF‐α) plays a crucial role in the pathophysiology of RA. It promotes inflammatory, apoptosis and necroptosis via TNF receptor‐1 (TNFR1) but elicit anti‐inflammatory effects via TNFR2. Herein, targeting TNFR2 has gained attention in RA studies. Understanding the role of nanomedicine in modulating TNFR2 signalling may be the instrument in development of RA therapies. Nanotechnology has made a significant progress in treating various conditions of diseases since its inception. Due to this, nanomedicine has emerged as a promising therapeutics approach for RA. Recent studies have demonstrated the potential of nanomedicine in RA theranostics, combining therapy and diagnostics for improved treatment outcomes. Owing to the challenges and advancements in the field of nanotechnology, nanoparticles are seen as an applicable candidate in the treatment of RA. In this review, we provide an overview of the role of nanomedicine in targeting TNFR2 for the treatment of RA and highlight the limitations of current therapies as well as the potential of nanocarriers with controlled drug release and active targeting abilities. Nanoparticles can direct T cells to develop into specific subsets when taken by antigen‐presenting cells. TNF‐α, a proinflammatory cytokine in rheumatoid arthritis disease, resembles to the expressed TNFR2 and triggers the activation of B cells, resulting in the inhibition of antibody production.